Media framing and the legitimation of repressive and persuasive policing in protest movements: A gamson–modigliani and rsa–isa analysis - Asrul M Mustaqim; Udi Rusadi; Sadakita Br Karo; Yuyun Rahmawati (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
In contemporary democracies, the legitimacy of protest and state authority is increasingly shaped not only through direct confrontation but through mediated discourse, raising critical questions about how meaning, power, and control are constructed in the public sphere. This study reconceptualizes media framing as an ideological mechanism that actively produces and stabilizes state legitimacy by examining representations of repressive and persuasive policing in protest coverage. Drawing on an integrated framework combining framing theory with Althusser’s concepts of Repressive State Apparatus and Ideological State Apparatus, this research employs a qualitative critical interpretive approach to analyze 24 news articles from leading Indonesian online media during protests surrounding the revision of the Corruption Eradication Commission Law and the Draft Criminal Code. The findings reveal a systematic discursive pattern in which demonstrations are reframed from democratic expressions into problems of disorder, privileging narratives of conflict while marginalizing political grievances. Within this structure, the police are consistently constructed as legitimate protectors, whereas demonstrators are positioned as sources of instability through delegitimizing language, visual cues, and causal narratives. The study further demonstrates how external actors are strategically invoked to explain violence and how persuasive policing is discursively framed as ineffective, thereby normalizing the transition toward coercive intervention. These results challenge the conventional view of media as neutral intermediaries and establish framing as a structural site where ideology and coercion converge. By advancing a critical synthesis of framing and state theory, this study contributes a novel conceptual perspective to global scholarship on media and power, demonstrating that legitimacy is dynamically produced through discursive alignment rather than inherently possessed by state institutions